1992
DOI: 10.1259/0007-1285-65-774-547
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic metastasis from renal cell carcinoma

Abstract: Pancreatic metastasis from renal cell carcinoma is exceptional, but may appear many years after initial diagnosis and radical nephrectomy of an apparently limited tumour. We report one case of an asymptomatic isolated pancreatic metastasis discovered fortuitously, 21 years after right radical nephrectomy for a low-grade renal cancer. In 1969, a 47-year-old man underwent right nephrectomy for renal cell carcinoma of “low-grade malignancy”. At this time, no metastases were evident and he remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…Gohij et al [4] reported 11 cases in 1990, Stankard and Karl [5] updated the number of cases to 16 in 1992, and the remaining cases were reported by Rypens et al [6], Takeuchi et al [7], Diaz Dominguez et al [8], Marcote Valdivieso et al [9], Reale et al [10], Dousset et al [11], Nakeeb et al [12], Sauvanet et al [13], and Badia et al [14]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gohij et al [4] reported 11 cases in 1990, Stankard and Karl [5] updated the number of cases to 16 in 1992, and the remaining cases were reported by Rypens et al [6], Takeuchi et al [7], Diaz Dominguez et al [8], Marcote Valdivieso et al [9], Reale et al [10], Dousset et al [11], Nakeeb et al [12], Sauvanet et al [13], and Badia et al [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a number of investigators claim that it is not necessary to perform FNAB in view of the fact that an aggressive surgical strategy can be taken for granted [12]. In this connection, analysis of the cases reported in the literature reveals that we can be sure that FNAB was performed only in 4 cases: in 2 of these the biopsy sample was hemorrhagic [6, 22], and in the other 2 it was diagnostic [5, 13]. In addition, we have to rule out the possibility of a primary pancreatic clear-cell cancer which would in any event be a rare variant of pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Since the interval between the primary diagnosis and metastatic disease can be long, [11,12] solitary metastasis to the pancreas often is an unsuspected clinical problem and is not high in the differential diagnoses of a pancreatic mass. [13,14] The mechanism of pancreatic metastases may involve direct invasion (tail involvement in left RCC) or lymphatic and hematogenous spread. Hematogenous spread is common when neoplastic thrombus is present in the renal vein.…”
Section: Discussionmentioning
confidence: 99%